농촌 거주 결혼이주여성의 우울에 미치는 영향요인 - 노소영(Roh, So Young); 김은영(Kim, Eun Young) (Sŏngin Kanho Hakhoe chi, 2012)
Purpose: This study aimed to identify factors influencing depression of married immigrant women in rural areas. Methods: The participants were 206 married immigrant women in Jeollanamdo, Korea. The data were collected using a structured questionnaire from November to December 2011 and analyzed using descriptive statistics, one-way ANOVA, Scheffe test, Pearson correlation coefficient, and stepwise multiple regression with SPSS/WIN 18.0. Results: The participants' mean age was 28.3 (range=20 to 49). Depression significantly differed according to age, spouse occupation, occupation and monthly household income. The depression was significantly correlated with acculturative stress, social support and marital satisfaction. Factors influencing depression were acculturative stress, social support and spouse occupation, which explained 42.9% of total variance. Acculturative stress was the most significant factor of all (${β}$=.41, p<.001). Conclusion: Based upon the findings, this study provides useful information that could assist in reducing the depression among married immigrant women, and indicates that nursing intervention is needed.